2008 2nd Electronics Systemintegration Technology Conference 2008
DOI: 10.1109/estc.2008.4684517
|View full text |Cite
|
Sign up to set email alerts
|

Distributed RLGC transient model of coupled interconnects in DSM chips for crosstalk noise simulation

Abstract: Noise effects in coupled interconnects, Le. crosstalk induced glitch and crosstalk induced delay can significantly impact the performance of deep sub-micron (DSM) chips. Therefore, in this paper distributed RLGC transient model of coupled interconnects has been developed that will be useful for analyzing such crosstalk noise effects in DSM chips. The model accuracy is quite comparable to the PSPICE simulation results and yet the simulation speed is at least 11 times faster than the latter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Comparing (16) with the ABCD model of a single interconnect provided in [3], it can concluded that decoupled per-unit-length resistance, inductance, conductance and capacitance for the equivalent victim model can be represented as: …”
Section: Coupled Interconnects and Decoupled Victim Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…Comparing (16) with the ABCD model of a single interconnect provided in [3], it can concluded that decoupled per-unit-length resistance, inductance, conductance and capacitance for the equivalent victim model can be represented as: …”
Section: Coupled Interconnects and Decoupled Victim Modelmentioning
confidence: 99%
“…Therefore, it is important to track down the limiting values/critical values of all such influencing (coupling) parasitic, below which a fault tolerant behavior of the device can be guaranteed. A comprehensive distributed crosstalk fault model similar to [3], which considers distributed RLGC parameters of two or more coupled interconnects, coupling parameters together with the strengths of the CMOS drivers and the receivers, is generally used for such simulation experiments. Though the model considered in [3] is very accurate but it requires simultaneous analysis of both victim and aggressor interconnects.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Crosstalk between transmission lines is one of most important SI issues and can not be neglected. The classic crosstalk theory based RLGC model which is acquired by estimating parasitic parameters( , , , R L G C ), assumes that electrical field coupling(capacitive coupling) and magnetic field coupling(inductive coupling) mainly contribute to the crosstalk issues [1], [2]. The RLGC model is simple and easy to use, however, there are shortcomings caused by the model itself.…”
Section: Introductionmentioning
confidence: 99%